The Burdens of Non-Communicable Disease, Cancer and Cardio-Oncology in Mongolia. - Batkhuyag, Nyamgerel; Namsrainaidan, Bayasgalan; Badrakh, Burmaa; Unurjargal, Tsolmon; Vanchin, Byambasuren (Central Asian Journal of Medical Sciences, 2019)
No abstract in English